Effect of Differences in Learning Treatments on the Mathematical Representation Ability of Elementary School Students - Vina Siti Nur Septiani; Maulana Maulana; Isrok'atun Isrok'atun (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Selecting an appropriate learning approach is important for developing students’ mathematical representation ability. This study aimed to examine and compare the effectiveness of three instructional treatments, namely the Realistic Mathematics Education (RME) approach integrated with the DASAFA (Dadu Sarapan Favorit) media, the RME approach without additional media, and the use of DASAFA media without the RME approach, in improving the mathematical representation ability of third-grade elementary school students on data presentation material. This study employed a quasi-experimental method with a nonequivalent pretest-posttest comparison-group design. The research subjects consisted of 115 students from four public elementary schools in North Sumedang District, divided into three experimental groups. The instruments used included a test measuring mathematical representation ability with a reliability of 0.923, as well as a learning interest questionnaire using a four-point Likert scale. Data analysis was conducted using the Kruskal-Walli’s test, N-Gain, and the coefficient of determination. The results showed significant differences in improvement among the three groups. The RME approach integrated with DASAFA media produced the greatest improvement, contributing 48.3% to students’ mathematical representation ability. The RME group contributed 38%, while the DASAFA media group contributed 15.4%. However, the DASAFA group achieved the highest visual representation score and the highest learning interest score of 87.03%. The findings suggest that integrating RME with contextual concrete media can support more meaningful mathematics learning, although students’ symbolic and verbal representation abilities still require further development.